A 6-year-old girl with vaginal spotting who was diagnosed with perivascular epithelioid cell neoplasm after vaginoscopic resection - Cho, Hyun-Jung (Korean Society of Obstetrics and Gynecology; Korean Society of Contraception and Reproductive Health; Korean Society of Gynecologic Endocrinology; Korean Society of Gynecologic Endoscopy and Minimal Invasive Surgery; Korean Society of Maternal Fetal Medicine; Korean Society of Ultrasound in Obstetrics and Gynecology; Korean Urogynecologic Society, 2014)
Perivascular epithelioid cell neoplasm (PEComa) is a rare tumor with unknown malignant potential. We report a case of a 6-year-old child with history of brain tumor (pineoblastoma), who presented with intermittent vaginal spotting for 6 months. A vaginoscopy revealed a 1.5×1.0-cm mass on the vaginal wall. Pathological examination demonstrated that the tumor was composed of clear cells with organoid patterns, which were immunohistochemically positive for HMB-45 and TFE3, and negative for CK, HNF1-B, SOX10, Melan A, and S-100 protein. These findings were consistent with PEComa arising from the vagina. Regular follow-up with magnetic resonance imaging has shown no signs of recurrence. This case shows that early detection of PEComa and subsequent regular follow-ups are important because of the neoplasm's unknown malignant potential.